Closing the Shop : Information Cartels and Japan's Mass Media - Freeman, Laurie Anne, 1957- (Book collections on Project MUSE., 2000)
"Closing the Shop shows us how the press system in Japan serves as neither a watchdog nor a lapdog. Nor does the state directly control the press in ways Westerners might think of as censorship. The level of interconnectedness, through both official and unofficial channels, helps set the agenda and terms of political debate in Japan's mass media to an extent that is unimaginable to many in the United States and other advanced industrial democracies. This fascinating look at Japan's information cartels helps to provide a critical, but often overlooked explanation for the overall power and autonomy enjoyed by the Japanese state."--Jacket